Test–retest reliability of approach‐avoidance conflict decision‐making during functional magnetic resonance imaging in healthy adults. Issue 8 (2nd March 2021) - McDermott, Timothy J.; Kirlic, Namik; Akeman, Elisabeth; Touthang, James; Clausen, Ashley N.; Kuplicki, Rayus; Aupperle, Robin L.
Abstract: Neural and behavioral mechanisms during approach‐avoidance conflict decision‐making are relevant across various psychiatric disorders, particularly anxiety disorders. Studies using approach‐avoidance conflict paradigms in healthy adults have identified preliminary neural mechanisms, but findings must be replicated and demonstrated as reliable before further application. This study sought to replicate previous findings and examine test–retest reliability of behavioral (approach behavior, reaction time) and neural (regions of interest [ROIs]) responses during an approach‐avoidance conflict task conducted during functional magnetic resonance imaging (fMRI). Thirty healthy adults completed an approach‐avoidance conflict task during fMRI on two occasions (mean interval: 17 days; range: 11–32). Effects of task condition during three task phases (decision‐making, affective outcome and monetary reward) and intraclass correlation coefficients (ICCs) were calculated across time points. Results replicated that approach behavior was modulated by conflict during decision‐making. ROI activations were replicated such that dorsal anterior cingulate cortex (dACC) was modulated by conflict during decision‐making, and dACC, striatum, and anterior insula were modulated by valence during affective outcomes ( p 's <.0083). Approach behavior during conflict demonstrated excellent reliability (ICCs ≥.77). Activation of dACC during conflict decision‐making and anterior insula during negative outcomes demonstrated fair reliability (ICCs = .51 and .54), and dACC and striatum activation demonstrated good reliability during negative outcomes (ICCs = .63 and .69). Two additional ROIs (amygdala, left dorsolateral prefrontal cortex) showed good reliability during negative outcomes (ICCs ≥.60). These results characterize several specific behavioral and neuroimaging responses that are replicable and sufficiently reliable during approach‐avoidance conflict decision‐making to support future utility. Abstract : The following article examines the test‐retest reliability of behavioral and neural responses to an approach‐avoidance conflict task during functional magnetic resonance imaging. Specific responses with sufficient reliability were characterized across multiple levels of analysis.